Factors Affecting Treatment Compliance In Tb Patients (Tuberculosis) During Pandemic Covid-19 At Labuang Baji Makassar Hospital - Imelda Appulembang; Ana Lita Luto Wujon; Dana Briggs; Maher Nasser Abdullah (International Journal of Health and Pharmaceutical (IJHP), 2021)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis (World Health Organization. Tuberculosis (TB) is also one of the main public health problems that has become one of the biggest threats in the world, in addition to the COVID-19 pandemic. Currently, TB (tuberculosis) is one of the risk factors for a person to be susceptible to being infected with COVID-19. The aim of the study was to determine the factors that influence medication adherence in TB (tuberculosis) patients during the Covid-19 pandemic at the LabuangBaji Hospital, Makassar. The research design used in this study is descriptive analytic research using a cross sectional study design. To determine the relationship between the independent variable and the dependent variable using joint measurements, the population is 128 people. respondents, the measuring instrument for measuring data is using a questionnaire. There is an influence between the knowledge variable about TB disease (tuberculosis) on the adherence to treatment of TB patients (tuberculosis) during the covid-19 pandemic at LabuangBaji Hospital Makassar showing a value (0.005 < 0.05), There is an influence between the variables of family support on treatment adherence TB patients (tuberculosis) during the covid-19 pandemic at LabuangBaji Hospital Makassar showed a value (0.003 < 0.05), There was an influence between the anxiety variable on adherence to treatment for TB patients (tuberculosis) during the covid-19 pandemic, LabuangBaji Hospital Makassar showed a value (0.001 < 0.05). There is an influence between knowledge of TB disease (tuberculosis), family support, anxiety and adherence to treatment for TB patients during the covid-19 pandemic at LabuangBaji Hospital Makassar.